BETWEEN VULNERABILITY AND CONTAMINATION: RETHINKING THE SELF IN THE GLOBAL AGE - Pulcini, Elena (Gênero & Direito, 2016)
Contemporary feminist thought undoubtedly has the merit of having called into question the paradigm of the modern subject: that is the figure of a sovereign subject. Despite immense differences, feminism has tried to rethink the subject by taking criticism of the modern paradigm as its starting point. The idea has emerged of a subject that takes leave of the modern Self’s unilateralism by reintegrating the excluded, repressed, undervalued poles (whether they are difference, the body, the unconscious or care). In other words, what has long been considered “other” loses its negative connotation and becomes an element constituting the Self. While sharing this perspective, I have come up with an idea that could be defined as the fertility of the negative. Particularly inspired by the reflection of Georges Bataille, I have tried to put forward the notion of a contaminated subject.